Slippery when wet: The free surface of the articular cartilage. Issue 6 (30th December 2020) - Raspanti, Mario; Protasoni, Marina; Zecca, Piero Antonio; Reguzzoni, Marcella
Abstract: The free surface of the articular cartilage must withstand compressive and shearing forces, maintain a low friction coefficient and allow oxygen and metabolites to reach the underlying matrix. In many ways it is critical to the physiology of the whole tissue and its disruption always involves deep pathological alterations and loss of the joint integrity. Being very difficult to image with section‐based conventional techniques, it was often described by previous research in conflicting terms or entirely overlooked. High‐magnification face‐on observations with high resolution scanning electron microscopy and with scanning probe microscopy revealed a very thin, delicate superficial layer rich in glycoconjugates, which may explain the very low friction coefficient of the tissue but which was very easily altered and/or dissolved in the preparation. Beneath this superficial sheet lies a thicker coat of thin, highly uniform, slightly wavy collagen fibrils lying parallel to the surface and mutually interconnected by a huge number of interfibrillar glycosaminoglycan bridges. These bridges and the collagen fibrils form an extended reticular structure able to redistribute tensile and compressive stress across a larger area of the surface and hence a greater volume of tissue. Abstract : The surface of the articular cartilage is covered by a thin, delicate layer very sensitive to preparation and easily altered or dissolved. Beneath lies a functionally continuous meshwork of thin collagen fibrils and glycosaminoglycan cross‐bridges.